2015
DOI: 10.3906/sag-1409-99
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and maximum standardized uptake values within lymph nodes of anthracosis diagnosed by endobronchial ultrasound-guided transbronchial needle aspiration

Abstract: Background/aim: Enlarged mediastinal lymph nodes can result from serious etiologies including granulomatous disease, neoplasia, etc., and a rare condition called anthracosis . The aim of this study was to determine the incidence of risk factors and the uptake values within the anthracotic lymph nodes.Materials and methods: 106 patients who underwent endobronchial ultrasound transbronchial needle aspiration and were diagnosed as having anthracosis were analyzed retrospectively. Patients with positive confirmati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…Some studies have reported increased FDG uptake in PET scans in anthracotic lymph nodes in the mediastinum. 5 In a study by Yilmaz Demirci et al 3 , the mean SUVmax value was reported as 4.76 (1-16.8) in anthracosis sampled lymph nodes. As a result, if there is a history of exposure to hazards and noxious particles, the possibility of a benign condition ought to be considered when serious uptake in mediastinal and hilar lymph nodes is observed in a PET scan.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Some studies have reported increased FDG uptake in PET scans in anthracotic lymph nodes in the mediastinum. 5 In a study by Yilmaz Demirci et al 3 , the mean SUVmax value was reported as 4.76 (1-16.8) in anthracosis sampled lymph nodes. As a result, if there is a history of exposure to hazards and noxious particles, the possibility of a benign condition ought to be considered when serious uptake in mediastinal and hilar lymph nodes is observed in a PET scan.…”
Section: Discussionmentioning
confidence: 96%
“…Anthracosis is also one of the common reasons for enlarged mediastinal lymph nodes in developing countries. 3 Anthracotic mediastinal lymph nodes often appear oval, with calcification. Sclerosing mediastinitis or mediastinal fibrosis terms are also used for “Fibrous mediastinitis.” In addition, it has been defined an as “idiopathic fibro-inflammatory lesion.” Even though the etiology has not been fully clarified, factors such as tuberculosis, aspergillosis, mucormycosis, blastomycosis, cryptococcosis, and anthracosis have been reported in the etiology of fibrous mediastinitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean SUVmax value of the patients with associated malignancy was 4.19 and the mean SUVmax of nonmalignant patients was 5.28. They found SUVmax values high in the group with anthracosis [ 15 ]. In their study, Köksal et al examined SUVmax values of metastatic, anthracotic, and reactive lymph nodes, which became definite after lymph node dissection in resected non-small cell carcinoma (NSCC) cases.…”
Section: Discussionmentioning
confidence: 99%
“…Por último, Saydam y colaboradores reportaron que la sensibilidad y especificidad de la estadificación mediastinal de pacientes trabajadores en minas de carbón con cáncer de pulmón de célula no pequeña (14,15,16), sea una entidad a tener en cuenta en los pacientes con era de 75% y 90%, respectivamente. Además, concluyó que el 18F-FDG PET-CT es insuficiente para la estadificación mediastinal en estos trabajadores por la alta tasa de falsos positivos debido a la presencia de neumoconiosis (17).…”
Section: Discussionunclassified